Flat slab strengthening techniques against punching-shear. (1st February 2019) - Lapi, Massimo; Ramos, António Pinho; Orlando, Maurizio
Highlights: Punching strengthening is required due to design/construction errors, load increase, etc. Strengthening techniques are compared using the Critical Shear Crack Theory. A case study is dealt with to give indications for strengthening pre-dimensioning. Predicted punching strength of strengthened slabs agrees with experimental data. A design tool is provided to choose which technique better fits the specific case. Abstract: Over the years, the flat slab system has become a popular form of construction in many countries, particularly for multi-storey buildings such as offices or carparks. Nowadays, a considerable number of flat slab buildings requires strengthening against punching. Reasons are several, like design or construction errors, poor quality materials, not complying with new codes provisions, or increase of vertical load. This paper discusses different techniques for strengthening of R/C slabs against punching: insertion of post-installed shear reinforcement, application of external fibre reinforced polymers or a bonded reinforced concrete overlay (BRCO) on the slab top surface, enlargement of the support, application of a post-tensioning system. The authors propose a unified approach, based on the Critical Shear Crack Theory (CSCT), to evaluate the effectiveness of each strengthening technique. The attempt is to give a reading key capable of adapting to different strengthening techniques and providing a comprehensive view of the problem. The study shows that the CSCT could be easily adapted to all strengthening techniques and punching strength predictions are in good agreement with literature experimental results. This work also proposes to give designers the tool to choose which strengthening technique suits better to the specific case.